PENGARUH KETERSEDIAAN KOLEKSI TERHADAP MINAT BACA PENGGUNA PERPUSTAKAAN DI BADAN PERPUSTAKAAN DAN ARSIP PROVINSI BALI - Martini, Kadek Sri (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2015)
ABSTRACT This research is descriptive quantitative aimed to describe the influence of independent variables on the dependent variable. The techniques of collecting data are questionnaires and literature study. The population are 5,892 and the number of samples are 361 based on krecjie table, set error rate is 5%. Sampling techniques is accidental sampling. Results of this research showed that the number of books in the library is inadequate, it can be seen from the library collections not varied and not up to date to answer the information needs of users.  The collections are not relevant, it can be analyzed from most of samples are students. Availability of book collections have effect to reading interest, it can be seen from the most of respondents (74,5%) agreed that reading interest can be arise due to the collections of the libraries are vary, up to date and having quality. Keywords: collection, reading interest, library